Answered

Welcome to Westonci.ca, the place where your questions are answered by a community of knowledgeable contributors. Get immediate and reliable solutions to your questions from a knowledgeable community of professionals on our platform. Discover detailed answers to your questions from a wide network of experts on our comprehensive Q&A platform.

You might need a calculator.

[tex]\[ g(t) = -(t-1)^2 + 5 \][/tex]

Over which interval does [tex]\( g \)[/tex] have an average rate of change of zero?

Choose 1 answer:
A. [tex]\( 1 \leq t \leq 4 \)[/tex]
B. [tex]\( -4 \leq t \leq -3 \)[/tex]
C. [tex]\( -2 \leq t \leq 0 \)[/tex]
D. [tex]\( -2 \leq t \leq 4 \)[/tex]


Sagot :

To determine over which interval the function [tex]\( g(t) = -(t-1)^2 + 5 \)[/tex] has an average rate of change of zero, we need to calculate the average rate of change for each given interval and see where it equates to zero.

The formula for the average rate of change of a function [tex]\( g(t) \)[/tex] between two points [tex]\( t_1 \)[/tex] and [tex]\( t_2 \)[/tex] is:
[tex]\[ \frac{g(t_2) - g(t_1)}{t_2 - t_1} \][/tex]

Let's calculate the average rate of change for each interval step-by-step.

### Interval A: [tex]\( 1 \leq t \leq 4 \)[/tex]

1. Calculate [tex]\( g(1) \)[/tex]:
[tex]\[ g(1) = -(1-1)^2 + 5 = 5 \][/tex]

2. Calculate [tex]\( g(4) \)[/tex]:
[tex]\[ g(4) = -(4-1)^2 + 5 = -(3)^2 + 5 = -9 + 5 = -4 \][/tex]

3. Average rate of change:
[tex]\[ \frac{g(4) - g(1)}{4 - 1} = \frac{-4 - 5}{3} = \frac{-9}{3} = -3 \][/tex]

### Interval B: [tex]\( -4 \leq t \leq -3 \)[/tex]

1. Calculate [tex]\( g(-4) \)[/tex]:
[tex]\[ g(-4) = -((-4)-1)^2 + 5 = -(5)^2 + 5 = -25 + 5 = -20 \][/tex]

2. Calculate [tex]\( g(-3) \)[/tex]:
[tex]\[ g(-3) = -((-3)-1)^2 + 5 = -(4)^2 + 5 = -16 + 5 = -11 \][/tex]

3. Average rate of change:
[tex]\[ \frac{g(-3) - g(-4)}{-3 - (-4)} = \frac{-11 - (-20)}{-3 + 4} = \frac{-11 + 20}{1} = \frac{9}{1} = 9 \][/tex]

### Interval C: [tex]\( -2 \leq t \leq 0 \)[/tex]

1. Calculate [tex]\( g(-2) \)[/tex]:
[tex]\[ g(-2) = -((-2)-1)^2 + 5 = -(3)^2 + 5 = -9 + 5 = -4 \][/tex]

2. Calculate [tex]\( g(0) \)[/tex]:
[tex]\[ g(0) = -((0)-1)^2 + 5 = -(1)^2 + 5 = -1 + 5 = 4 \][/tex]

3. Average rate of change:
[tex]\[ \frac{g(0) - g(-2)}{0 - (-2)} = \frac{4 - (-4)}{0 + 2} = \frac{4 + 4}{2} = \frac{8}{2} = 4 \][/tex]

### Interval D: [tex]\( -2 \leq t \leq 4 \)[/tex]

1. Calculate [tex]\( g(-2) \)[/tex] (previously calculated as -4).

2. Calculate [tex]\( g(4) \)[/tex] (previously calculated as -4).

3. Average rate of change:
[tex]\[ \frac{g(4) - g(-2)}{4 - (-2)} = \frac{-4 - (-4)}{4 + 2} = \frac{-4 + 4}{6} = \frac{0}{6} = 0 \][/tex]

### Conclusion
The interval over which the function [tex]\( g(t) = -(t-1)^2 + 5 \)[/tex] has an average rate of change of zero is:

[tex]\[ \boxed{-2 \leq t \leq 4} \][/tex]